Thermal Transport in Two-Dimensional Heterostructures - Chen, Xue-Kun; Zeng, Yu-Jia; Chen, Ke-Qiu (Frontiers in Materials, 2020)
Heterostructures based on two-dimensional (2D) materials have attracted intense attention in recent decades due to their unusual and tunable physics/chemical properties, which can be converted into promising engineering applications ranging from electronics, photonics, and phononics to energy recovery. A fundamental understanding of thermal transport in 2D heterostructures is crucial importance for developing micro-nano devices based on them. In this review, we summarized the recent advances of thermal transport in 2D heterostructures. Firstly, we introduced different theoretical methods and experimental techniques for thermal transport in low-dimensional materials. Then we briefly reviewed the thermal properties of various 2D single-phase materials beyond graphene such as hexagonal boron nitride (h-BN), phosphorene, transition metal dichalcogenides (TMDs) and borophene, and emphatically discussed various influencing factors including structural defects, mechanical strain, and substrate interactions. Moreover, we highlighted thermal conduction control in tailored nanosystems—2D heterostructures and presented the associated underlying physical mechanisms, especially interface-modulated phonon dynamics. Finally, we outline their significant applications in advanced thermal management and thermoelectrics conversion, and discuss a number of open problems on thermal transport in 2D heterostructures.